Vestibulo-Hippocampal Function Is Enhanced and Brain Structure Altered in Professional Ballet Dancers - Dordevic, Milos; Schrader, Robert; Taubert, Marco; Müller, Patrick; Hökelmann, Anita; Müller, Notger G. (Frontiers in Integrative Neuroscience, 2018)
Background and objective Life-long balance training has been shown to affect brain structure, including the hippocampus. Data are missing in this respect on professional ballet dancers of both genders. It is also unknown whether transfer effects exist on general balancing as well as spatial orientation abilities, a function mainly supported by the hippocampus. We aimed to assess differences in gray matter structure, general balancing skills and spatial orientation skills between professional ballet dancers and non-dancers. Methods Nineteen professional ballet dancers aged 18-35 (27.5 ± 4.1 years; 10 females) and nineteen age-matched non-dancers (26.5 ± 2.1 years; 10 females) were investigated. Main outcomes assessed were the score of a 30-item clinical balance test (CBT), the average error distance (in centimeters) on triangle completion task and difference in gray matter density (GM) as seen by voxel-based morphometric analysis (VBM, SPM). Results Ballet group performed significantly better on all conditions of the CBT and in the wheelchair (vestibular-dependent) condition of the spatial orientation test (OT). Larger GM volumes for ballet dancers were observed in the right hippocampus, parahippocampal gyrus, insula and cingulate motor cortex, whereas both larger and smaller volumes were detected within cerebellum bilaterally in comparison to non-dancers. Conclusion Our results indicate that life-long ballet training could lead to better clinically relevant balancing abilities as well as vestibular-dependent spatial orientation capabilities; both of the benefits might be caused by positive influence of ballet training on the vestibular system function, and - possibly - its connectivity with temporal lobe regions responsible for vestibular-dependent orienting in space.